Dust remobilization from rough planar surfaces in tokamak steady-state plasmas. (December 2018) - Autricque, A.; Peillon, S.; Gensdarmes, F.; Sow, M.; Fedorczak, N.; Roche, H.; Pluchery, O.; Grisolia, C.
Highlights: Adhesion forces distributions between tungsten spheroids and a tungsten roughness of tokamakrelevant roughness are measured using atomic force microscopy. The van der Waals-based Rabinovich model is shown to reasonably reproduce the mean adhesion force, while a fit (using a Biasi like function) for the spread is proposed. External forces applied on a dust particle located on a tokamak divertor are estimated using a simple sheath model. Typical tokamak tungsten dust is shown to be remobilizable by reasonable sheath electric fields. Abstract: The ability of tungsten (W) dust to be remobilized from rough tokamak plasma-facing surfaces is investigated in this study. Atomic Force Microscopy is used to evaluate the adhesion force distribution between W spheroids of ∼ 1 − 10 µm radius and a rough W substrate. Our results confirm that the Rabinovich model describes reasonably well the mean adhesion force in tokamak-relevant surface roughness regimes. The external (electric and ion drag) forces are estimated as well using a simplified sheath model. The results reveal that micron-size dust can be resuspended by attainable electric fields in tokamak conditions.